Presentation, Clinical Profile, and Prognosis of Young Patients With Myocardial Infarction With Nonobstructive Coronary Arteries (MINOCA): Results From the VIRGO Study - Safdar, Basmah (J Am Heart Assoc, 2018)
BACKGROUND: We compared the clinical characteristics and outcomes of young patients with myocardial infarction with nonobstructive coronary arteries (MINOCA) versus obstructive disease (myocardial infarction due to coronary artery disease [MI‐CAD]) and among patients with MINOCA by sex and subtype. METHODS AND RESULTS: Between 2008 and 2012, VIRGO (Variation in Recovery: Role of Gender on Outcomes of Young AMI Patients) prospectively enrolled acute myocardial infarction patients aged 18 to 55 years in 103 hospitals at a 2:1 ratio of women to men. Using an angiographically driven taxonomy, we defined patients as having MI‐CAD if there was revascularization or plaque ≥50% and as having MINOCA if there was <50% obstruction or a nonplaque mechanism. Patients who did not have an angiogram or who received thrombolytics before an angiogram were excluded. Outcomes included 1‐ and 12‐month mortality and functional (Seattle Angina Questionnaire [SAQ]) and psychosocial status. Of 2690 patients undergoing angiography, 2374 (88.4%) had MI‐CAD, 299 (11.1%) had MINOCA, and 17 (0.6%) remained unclassified. Women had 5 times higher odds of having MINOCA than men (14.9% versus 3.5%; odds ratio: 4.84; 95% confidence interval, 3.29–7.13). MINOCA patients were more likely to be without traditional cardiac risk factors (8.7% versus 1.3%; P<0.001) but more predisposed to hypercoaguable states than MI‐CAD patients (3.0% versus 1.3%; P=0.036). Women with MI‐CAD were more likely than those with MINOCA to be menopausal (55.2% versus 41.2%; P<0.001) or to have a history of gestational diabetes mellitus (16.8% versus 11.0%; P=0.028). The MINOCA mechanisms varied: a nonplaque mechanism was identified for 75 patients (25.1%), and their clinical profiles and management also varied. One‐ and 12‐month mortality with MINOCA and MI‐CAD was similar (1‐month: 1.1% and 1.7% [P=0.43]; 12‐month: 0.6% and 2.3% [P=0.68], respectively), as was adjusted 12‐month SAQ quality of life (76.5 versus 73.5, respectively; P=0.06). CONCLUSIONS: Young patients with MINOCA were more likely women, had a heterogeneous mechanistic profile, and had clinical outcomes that were comparable to those of MI‐CAD patients. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00597922.